Parenting Patterns with Sibling Rivalry Incidents in Preschooler: A Systematic Review - Nessy Anggun Primasari; Siti Riskika; Niswa Salamung; Melinda Restu Pertiwi (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: Parenting style is a comprehensive unity between parent-child interactions. Different parenting styles in children have an impact on the incidence of sibling rivalry in preschool children. According to WHO (World Health Organization) the incidence of sibling rivalry in parenting, the known data from research on 52 respondents: democratic parenting (32.7%), authoritarian (3.8%), permissive (46.2%), abandonment (17.3%), there was Sibling Rivalry (65.4%) and there was no Sibling Rivalry (34.6%). This paper aims to assess the effect of parenting style on the incidence of sibling rivalry in preschool children. Method: This writing uses a systematic review design. The data is taken from the Science Direct, Poquest and Google Cendikia databases, with a period of 2016-2020. Search for journals and articles using the keywords parenting (parenting), sibling rivalry, prescooler (pre-school children). Result: There were ten selected journal articles from 2508 journal articles found from three databases. All journal articles say that there is a relationship between the type of parenting style of parents and the incidence of sibling rivalry in preschool children. Discussion: The results of the analysis in this systematic review show that modern parents, who have a level of knowledge that continues to develop, are more proactive in seeking information about parenting styles and sibling rivalry. Conclusion: The majority of parenting styles adopted by parents are democratic parenting so that parents become more pro-active in seeking information about the best parenting styles and the incidence of sibling rivalry.